Modul matematika pada materi relasi dan fungsi untuk siswa MTs kelas VIII berbasis kontekstual dan terintegrasi nilai-nilai keislaman - Atsnan, Muh. Fajaruddin (Universitas PGRI Kalimantan, 2023)
This research aims to describe the development of mathematics teaching materials in the form of modules based on a contextual approach integrated with Islamic values for relationship and function material, and to obtain information on the quality of the modules created. This module covers Islamic values, such as prayer, almsgiving, the good qualities of the Prophet, as well as good habits dictated by religion. This research and development model follows the ADDIE reference. The research results explain that (1) the validity of the module is in the